Analysis of The Quality of Dribbling Techniques of Inspire Club Futsal Athletes Based on The Time Take to Complete Tests with and Without The Ball - Zalfa Lathifah Supyana; Iman Imanudin; Unun Umaran (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
This study aims to analyze the quality of dribbling techniques of female athletes of  the Inspire club based on the comparison of travel time in the zig-zag test with the ball and without the ball as an objective indicator of technical ability. This study uses a quantitative method with a descriptive – comparative approach. The research subjects amounted to 15 female futsal athletes of the Inspire Club who were selected using purposive sampling techniques. The instrument in this study is in the form of a zig-zag dribbling test with the ball and without the ball, with the main measurement variable being travel time. The data analysis used was descriptive statistics and the Paired Sample T-Test test to determine the difference in performance between the two test conditions. The results showed that the average dribbling time with the ball (19.82 ± 2.96 seconds) was significantly slower than that of the test without the ball (13.07 ± 1.11 seconds). The results of the statistical test found that there was a significant difference between the two tests (p < 0.05). This shows that the ability of athletes to maintain speed when carrying the ball is not optimal. These findings show an imbalance between the ability to run speed without the ball and dribbling skills when carrying the ball.  Based on these results, it can be concluded that the quality of the dribbling technique of Inspire Club futsal athletes has not developed in line with the ability to run speed without the ball, so a more specific, progressive, and game-like training program is needed to improve ball possession at high speed.